2020
DOI: 10.7150/ijbs.44343
|View full text |Cite
|
Sign up to set email alerts
|

A new SIRT1 inhibitor, MHY2245, induces autophagy and inhibits energy metabolism via PKM2/mTOR pathway in human ovarian cancer cells

Abstract: Ovarian cancer is a common gynecological cancer that is found worldwide. Class III histone deacetylase (HDAC) inhibitors, a new class of anticancer agents, induce autophagy in various human cancer cells. The aim of the present study was to investigate the antitumor activity of MHY2245, a new synthetic SIRT inhibitor, on human ovarian cancer cells. We found that MHY2245 exhibited potent cytotoxicity to SKOV3 cells in a time-and concentration-dependent manner. The cytotoxicity of MHY2245 (IC 50 =0.32 µM) was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…apoptosis or autophagy (Carafa et al, 2018(Carafa et al, , 2019De et al, 2018;Tae et al, 2018Tae et al, , 2020Igase et al, 2020).…”
Section: Efficiency Of Hdacimentioning
confidence: 99%
See 1 more Smart Citation
“…apoptosis or autophagy (Carafa et al, 2018(Carafa et al, , 2019De et al, 2018;Tae et al, 2018Tae et al, , 2020Igase et al, 2020).…”
Section: Efficiency Of Hdacimentioning
confidence: 99%
“…HDACi can also induce DNA damage, cell cycle arrest, apoptosis and autophagy to promote cancer cell death mentioned above. Some novel SIRT inhibitors, such as MC2494, MHY2245, MHY2256, tenovin-6, and YC8-02, also perform diverse anti-tumor activities through mediating apoptosis or autophagy ( Carafa et al, 2018 , 2019 ; De et al, 2018 ; Tae et al, 2018 , 2020 ; Li M. et al, 2019 ; Igase et al, 2020 ).…”
Section: Hdac Inhibitors In Cancer Therapymentioning
confidence: 99%
“…It is well known that autophagy plays a dual role in tumor development. It can serve as either a tumor suppressor to inhibit tumor progression or a cell survival enhancer to promote tumor growth [39,40]. On the one hand, autophagy recycles damaged cell components and provides substrates for biosynthesis and energy metabolism [39].…”
Section: Discussionmentioning
confidence: 99%
“…PKM2’s role in aerobic glycolysis and cancer metabolism has been the focus of most of the literature and research to date [ 28 , 29 , 71 , 143 ]. Xenograft studies in mice injected with H1299 lung cancer cells overexpressing the mouse PKM1 or PKM2 isoforms then stably knocked down for the endogenous PKM2 revealed that PKM2 is necessary for aerobic glycolysis.…”
Section: “Metabolic” and “Non-metabolic” Functions Of Pkm2mentioning
confidence: 99%